If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(7 + x) + 5x = 0 (7 * 6 + x * 6) + 5x = 0 (42 + 6x) + 5x = 0 Combine like terms: 6x + 5x = 11x 42 + 11x = 0 Solving 42 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 11x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + 11x = 0 + -42 11x = 0 + -42 Combine like terms: 0 + -42 = -42 11x = -42 Divide each side by '11'. x = -3.818181818 Simplifying x = -3.818181818
| -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 | | 176+4= | | 5x=7y+28 | | 9+5a=2a+5 | | 2x-1/3x=15 | | (3/8)(8/3)(n) | | (5/16)+(2/3)x=(1/4)-(1/6)x | | (-72)+36= | | (3/8)(8/3) | | A/4+7=22 | | 1-1/2-1/3 | | 2(0.6x+x)= | | (3k-3)(7k+7)= | | -8=p-5 | | -10b+2b+b=0 | | 5x+17x-8=180 | | 2(1.2)= | | (-76)+(-84)= | | (3x-6)(3x-6)=0 | | 27-9x=4x+8 | | 4(x+9)+5x= | | 2x-5=?(x+4) | | (-15)+(-7)= | | 21x^4=2+x^2 | | 2-8x/1 | | 4(x+5)=3(x-6)+x | | -2(7-y)+4=44 | | 5/16*40n | | 6b^2-40=-8b+2b^2 | | .2-y=-.05x |